Axiological contexts of geographical cognition - Viacheslav D. Sukhorukov; Yuriy N. Gladkiy; Valeriy G. Suslov (European Journal of Geography)
The paper reasons about value consciousness, which plays a special role in the study and development of geographical space. The understanding of geographical space is based on multidimensional analytical features of this subject category. Geographical space is represented as an area of mutual penetration of a unique natural shell and an original anthroposphere. In this fusion of nature and society, the predominant role of humans in the surrounding reality is highlighted. It is suggested that the urgent task of geographical knowledge is the need to unite knowledge about people, nature and society in the conditions of spatial interaction. It is emphasized that the main vector of modern geographical research is the conceptual progress from "Earth" to "Person" as the only reliable wealth that the world possesses. The dominant role of a person in the surrounding reality is determined by the moral consciousness and reasonable practice of an individual in specific spatial circumstances. The authors illustrate that in modern conditions it is impossible to do this without appealing to humanitarian values, which become the fundamental basis of the entire world "Dasein” (by M. Heidegger) as an existing being.